2021
DOI: 10.1021/acscatal.1c01921
|View full text |Cite
|
Sign up to set email alerts
|

Controllable Synthesis of Vacancy-Defect Cu Site and Its Catalysis for the Manufacture of Vinyl Chloride Monomer

Abstract: Designing favorable structures of active sites and clarifying the structure− activity relationship are important to narrow the large activity gap between Cu-based and the noble-metal-based catalytic systems for vinyl chloride production. Herein, we report a facile controllable thermal method for fabricating the platform of Cu single-atom catalysts ranging from the standard no-vacancy-defect CuCl 3 −N to vacancy-defect CuCl 2 V−N ("V" for the vacancy-defect site) and to no-vacancy-defect CuN 4 . The gradually r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…25 Wang et al synthesized vacancy-defective CuCl 2 V-N SAC catalysts via a thermal method and found that the activation of C 2 H 2 adsorption at the defect sites could reduce the reaction energy barrier and the formation of vacancy defects narrowed the activity difference between Cu-based catalysts and precious metal catalysts. 26 Adjusting the electronic properties of the main active constituents by adding metal electronic components is another approach to improve the catalyst performance. For example, Zhai et al introduced cesium (Cs) additives to prepare CsCuCl 3 nanoparticles loaded on activated carbon, which maintained a C 2 H 2 conversion of about 92% for 200 h at 200 °C and an industrial GHSV of 50 h −1 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…25 Wang et al synthesized vacancy-defective CuCl 2 V-N SAC catalysts via a thermal method and found that the activation of C 2 H 2 adsorption at the defect sites could reduce the reaction energy barrier and the formation of vacancy defects narrowed the activity difference between Cu-based catalysts and precious metal catalysts. 26 Adjusting the electronic properties of the main active constituents by adding metal electronic components is another approach to improve the catalyst performance. For example, Zhai et al introduced cesium (Cs) additives to prepare CsCuCl 3 nanoparticles loaded on activated carbon, which maintained a C 2 H 2 conversion of about 92% for 200 h at 200 °C and an industrial GHSV of 50 h −1 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…28 Recently, the vacancy-defect Cu site catalyst synthesized by Li et al could significantly reduce the activity gap between Cu-and noble-metal-based systems from 37 to 1.5 times, which fully demonstrates the potential of Cu single-atom catalysts. 29 It's generally known that single-atom catalysts' performance is closely related to their well-defined structure and coordination environment; 30 therefore, exploring the effect of different heteroatoms' coordination on the performance is crucial for the design of Cu single-atom catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…It is also widely used in construction, agriculture, daily necessities, and other fields due to its electrical insulating characteristics, flame retardancy, and corrosion resistance . Vinyl chloride can be synthesized by the calcium carbide acetylene process, ethane process, or petroleum ethylene process, , among which the calcium carbide acetylene process is popular in areas with rich coal resources; however, the use of volatile and highly toxic mercury chloride catalyst makes the reaction process antithetical to “green” concepts. , Therefore, it is important to identify environmentally friendly catalysts for the hydrochlorination of acetylene to replace the HgCl 2 catalyst. , For decades, researchers have focused on the selection and optimization of metal catalysts, especially Au-, Ru-, , Cu-, and Pd-based catalysts, which usually exhibit excellent catalytic performance; however, these metal catalysts have several shortcomings, including high prices, easy agglomeration, loss, etc . Compared with metal catalysts, environmentally friendly carbon materials with features of high surface area, tunable pore structure, mechanical/chemical strength, etc.…”
Section: Introductionmentioning
confidence: 99%